What activates thermogenesis when lipid droplet lipolysis is absent in brown adipocytes?. (3rd April 2018) - Shin, Hyunsu; Shi, Hang; Xue, Bingzhong; Yu, Liqing
ABSTRACT: Cold exposure activates the sympathetic nervous system. It is generally thought that this sympathetic activation induces heat production by stimulating lipolysis of cytosolic lipid droplets (LDs) in brown adipocytes. However, this concept was not examined in vivo due to lack of appropriate animal models. Recently, we and others have demonstrated that LD lipolysis in brown adipocytes is not required for cold-induced nonshivering thermogenesis. Our studies uncovered an essential role of white adipose tissue (WAT) lipolysis in fueling thermogenesis during fasting. In addition, we showed that lipolysis deficiency in brown adipose tissue (BAT) induces WAT browning. This commentary further discusses the significance of our findings and how whole body may be heated up without BAT lipolysis.